2013
DOI: 10.4300/jgme-d-13-00072.1
|View full text |Cite
|
Sign up to set email alerts
|

“Best Practice” for Patient-Centered Communication: A Narrative Review

Abstract: Background Communicating with patients has long been identified as an important physician competency. More recently, there is a growing consensus regarding the components that define physician-patient communication. There continues to be emphasis on both the need to teach and to assess the communication skills of physicians. Objective This narrative review aims to summarize the work that has been conducted in physician-patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
328
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(337 citation statements)
references
References 87 publications
3
328
0
6
Order By: Relevance
“…Interaction and communication between patient and doctor in clinical encounters are integral to how health services work (King & Hoppe, 2013). Strong and collaborative doctor-patient partnerships can mitigate the challenges brought by the lack of clarity, and thereby reduce detrimental effects of medical uncertainty (Kornelsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interaction and communication between patient and doctor in clinical encounters are integral to how health services work (King & Hoppe, 2013). Strong and collaborative doctor-patient partnerships can mitigate the challenges brought by the lack of clarity, and thereby reduce detrimental effects of medical uncertainty (Kornelsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another way to improve physician-patient communication is to enhance the teaching of communication skills during undergraduate medical education [2]. This is particularly important, as studies have shown that students become more cynical and less empathetic during medical school [23].…”
Section: Making a Change: Methods To Improve Communication With Patientsmentioning
confidence: 99%
“…Although communication is recognized as an important physician competency, physicians are not well trained to communicate effectively [2]. Additionally, physicians' position of authority in the physician-patient relationship may intimidate some patients, rendering them overly deferential or susceptible to undue influence in health care decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of all adults in the United States over 50 have significant hearing loss 8,9 that can lead to problems understanding spoken discourse even under quiet listening conditions. 9 Like closed captioning on television, speech-to-text devices can be used to improve comprehension of everyday conversations by the hearing impaired.…”
Section: Introductionmentioning
confidence: 99%